Feasibility of daylight‐mediated photodynamic therapy for actinic keratosis throughout the year in Central and South America: a meteorological study. (7th April 2016) - Grinblat, Beni; Galimberti, Gaston; Pantoja, Gonzalo; Sanclemente, Gloria; Lopez, Miguel; Alcala, Daniel; Torezan, Luís; Kerob, Delphine; Pascual, Thierry; Chouela, Edgardo
Summary: Background: Daylight‐mediated photodynamic therapy (DL‐PDT) is an efficacious treatment option for thin actinic keratosis (AK) that offers advantages over conventional PDT in terms of tolerability, treatment duration, and cost. A clinical study conducted in Australia determined the mean irradiance during a 2‐hour exposure to be 305.8 W/m 2 (range: 40–585 W/m 2 ). The protoporphyrin IX light dose is influenced by latitude, weather conditions, and time of year. A recent study of meteorological data concluded that DL‐PDT can be performed effectively throughout the year in Australia. Objectives: Based on the same hypothesis and applying the same methodology, the present study investigated the suitability of daylight to perform DL‐PDT in Central and South America. Methods: Solar radiation and weather data were gathered and analyzed to assess daylight irradiance (light intensity) throughout a full year across 32 geographical locations in Central and South America. Results: The minimum average daily solar irradiance reported was above 305.8 W/m 2 in all locations investigated throughout the year. Annual averages of daily irradiance ranged from 578 W/m 2 in Chihuahua, Mexico, to 321 W/m 2 in Puerto Montt, Chile. Conclusions: Daylight‐mediated PDT for AK can be performed effectively throughout the year in Central and South America given that weather conditions permit a comfortable 2‐hour direct exposure to daylight.